Implementation of Dividend Policy in Sharia Fund Sources - Muhammad Rijalus Sholihin (LPPM Institut Teknologi dan Sains Mandala, 2023)
Sharia banks are financial entities that act as part of the economic sector in a country. Evaluation of the value of shares is crucial in the company's journey. Dividend policy has an important role in determining share value, creating a balance between current dividend distribution and retained earnings to maximize share value. In this context, there are two main options regarding the management of net income after tax: first, distribution to share owners as dividends; second, reinvestment as retained profits. Therefore, dividend policy is an important basis in dealing with how after-tax profits are treated, whether as dividends or reinvestment. This is a key element in the company's strategy to maintain and increase the value of its shares.